Dinâmica de populações arbóreas em área de cerrado sujeito ao fogo - Leite, Marcelo Boccia (2010)
Fire is a common disturbance in the Brazilian savanna and their action can affect important parameters and, consequently, the rate of population growth. The matrix models are powerful tools for studies of population dynamics, this models provide a projection of the rate of population growth. The aim of this study was to investigate the influence of fire on the population growth rate through the use of matrix models. The study was carried out in the cerrado sensu stricto site in southeastern Brazil. The individuals Anadenanthera falcata, Dalbergia miscolobium and Xylopia aromatica were divided on class size and populations growth rates were found through the model matrix Lefkovitch. There was an increase in the number of seedlings and sprouts between intervals studied. The rates of population growth remained close to 1; the survival of adults was fundamental population growth of X. aromatica. We can conclude that the fire favored vegetative reproduction and sexual differently among species, and that sexual reproduction was more intense in D. miscolobium. The growth rates indicate that the three species are resilient to fire and the vegetative reproduction contributed little to the population growth of X. aromatica, indicating that adult survival is important for the establishment of this species.